2012
DOI: 10.1186/1750-1172-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine supplementation in a child with inherited GS deficiency improves the clinical status and partially corrects the peripheral and central amino acid imbalance

Abstract: Glutamine synthetase (GS) is ubiquitously expressed in mammalian organisms and is a key enzyme in nitrogen metabolism. It is the only known enzyme capable of synthesising glutamine, an amino acid with many critical roles in the human organism. A defect in GLUL, encoding for GS, leads to congenital systemic glutamine deficiency and has been described in three patients with epileptic encephalopathy. There is no established treatment for this condition.Here, we describe a therapeutic trial consisting of enteral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…2 Later, we reported two more cases from the same family with similar clinical features and, for the first time, cerebrospinal fluid findings were reported on the two siblings with low asparagine levels. 3 The pathophysiology of the disease was suggested as being due to asparagine deficiency similar to glutamine 4 and serine synthesis defects. 5 The possibility of neurotoxicity from excessive excitatory neurotransmitters was entertained as well.…”
Section: Introductionmentioning
confidence: 99%
“…2 Later, we reported two more cases from the same family with similar clinical features and, for the first time, cerebrospinal fluid findings were reported on the two siblings with low asparagine levels. 3 The pathophysiology of the disease was suggested as being due to asparagine deficiency similar to glutamine 4 and serine synthesis defects. 5 The possibility of neurotoxicity from excessive excitatory neurotransmitters was entertained as well.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine use was evaluated in a clinical trial with children in severe disease states. The results demonstrated that it has a beneficial effect on brain activity and the decrease of ammonia in the body 4 . Furthermore, the findings indicated that glutamine is systemically safe and could be administered in different ways 4,5 .…”
Section: Introductionmentioning
confidence: 84%
“…In contrast, N-of-1 studies involve trial, assessment, and modification of care in an individual patient. In the context of research, N-of-1 trials are generally published as case reports [15][16][17][18][19]. Gabler et al [20] and Duan et al [21] recently published a comprehensive review of single patient trials.…”
Section: N-of-1 Studies Prior To the Era Of Genomic Medicinementioning
confidence: 99%